Dendrite‐Free Metallic Lithium in Lithiophilic Carbonized Metal–Organic Frameworks. Issue 18 (24th March 2018) - Zhu, Mengqi; Li, Bin; Li, Songmei; Du, Zhiguo; Gong, Yongji; Yang, Shubin
Abstract: Although metallic lithium is a promising anode material due to its high theoretical capacity, the uncontrollable growth of lithium dendrites and infinite volume change hamper its practical applications. Here, the lithiophilic property of carbonized metal–organic frameworks (cMOFs) is harnessed with zinc species to achieve a uniform lithium‐cMOFs (Li‐cMOFs) hybrid via a molten lithium infusion approach. In the resultant Li‐cMOFs, not only are abundant Zn clusters are uniformly confined and dispersed in the matrix, serving as homogeneous nucleation sites to guide Li deposition, but also the 3D conductive porous structure enables the homogenization of the distributions of electric field and Li ion flux, avoiding the formation of lithium dendrites. Hence, this hybrid exhibits superior electrochemical performance with a very low voltage hysteresis and a good cycle life. This provides a new manner to achieve a series of stable metallic lithium anodes based on the large family of metal–organic frameworks with tunable metal species. Abstract : A uniform Li‐cMOFs hybrid with abundant homogeneously dispersed Zn clusters and 3D conductive structure is achieved. Such unique features not only enable the guiding of nucleation and the growth of metallic lithium inside cMOFs, but also efficiently inhibit the volume change of lithium during stripping/plating processes. Consequently, this hybrid exhibits good electrochemical performance including low voltage hysteresis and long cycle life.